2021
DOI: 10.3389/fonc.2021.654285
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Full Lymphadenectomies in Intermediate- and High-Risk Endometrial Cancer by Sentinel Lymph Node Biopsy Implementation

Abstract: ObjectiveTo evaluate the role of sentinel lymph node biopsy (SLNB) to avoid staging lymphadenectomies by detecting nodal metastasis in intermediate- and high-risk endometrial cancer (EC).MethodsA single institutional retrospective study was performed including all patients with intermediate- and high-risk EC who underwent surgical nodal staging between January 2012 and December 2019. Patients with disseminated disease detected on imaging techniques or at the time of surgery were excluded. Patients were evaluab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
5
1
2
Order By: Relevance
“…This finding is higher than that reported in the FIRES trial 8 . However, Pineda et al 27 reported an FNR of 10% for intermediate‐risk EC and 14.3% for high‐risk EC, which is a higher rate than our findings. The main difference in our study is that not all patients underwent complete lymphadenectomy after SLN biopsy because the main objective of our study was to compare oncological outcomes between the two groups.…”
Section: Discussioncontrasting
confidence: 95%
“…This finding is higher than that reported in the FIRES trial 8 . However, Pineda et al 27 reported an FNR of 10% for intermediate‐risk EC and 14.3% for high‐risk EC, which is a higher rate than our findings. The main difference in our study is that not all patients underwent complete lymphadenectomy after SLN biopsy because the main objective of our study was to compare oncological outcomes between the two groups.…”
Section: Discussioncontrasting
confidence: 95%
“…Pineda et al recently studied whether systematic lymphadenectomy could be avoided by performing a single SLN biopsy. They found an overall sensitivity of 85% and a false negative rate of 15% in their population of patients with high-risk endometrial cancer (all stages) (22). On another note, the success of SLN biopsy does not appear to be influenced by BMI (23,24), and a Canadian study showed that obese women who underwent SLN biopsy without complete lymphadenectomy presented fewer operative adverse events and that their survival was not impacted (25).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the percentage of women with positive nodes missed does not differ according to the tracer used. What has been shown is that at the initial stages of ICG, using a learning curve, a higher number of SLNs are identified, which decreases with the surgeon’s experience, being reduced to the minimum over years of experience of our center, with the use of IC, currently being more precise [ 36 ]. Our median SLN node number seen intraoperatively with ICG was 2 (2–3) compared to 3 (2–4) using the double-tracer technique ( p = 0.006).…”
Section: Discussionmentioning
confidence: 99%